Benefits of Prophylactic Cranial Irradiation in the MRI Era for Patients With Limited Stage Small Cell Lung Cancer - Qi, Chao; Li, Wang; Li, Hanming; Wen, Fengyun; Zhou, Lu; Sun, Xiaohu; Yu, Hong (Frontiers in Oncology, 2022)
Abstract Purpose: Previous studies have shown that prophylactic cranial irradiation (PCI) can improve the survival of patients with limited-stage small cell lung cancer (LS-SCLC). PCI is recommended for patients who respond well to chemoradiotherapy. However, whether PCI could be extrapolated to the LS-SCLC patients in the modern era of magnetic resonance imaging (MRI) is unknown. This study aimed to explore the value of PCI in patients with LS-SCLC in the era of brain MRI. Methods: This study included 306 patients with LS-SCLC at the Cancer Hospital of China Medical University. All patients received brain MRI at diagnosis and after radiochemotherapy to exclude brain metastases. A propensity score matching was performed to reduce the influence of potential confounders. Overall survival (OS) , progression-free survival (PFS) and recurrence failure types were compared between PCI and non-PCI groups. Results: Among the 306 eligible patients, 81 underwent PCI and 225 did not. After propensity score matching, there was no statistical difference in baseline data between the two groups, with 75 patients in each group. PCI did not achieve OS (median OS:35 vs. 28 months, P=0.128) or PFS (median PFS:15 vs. 12 months, P=0.339) benefits. During follow-up, 30 patients (20.0%) developed brain metastases, including 13 patients (17.3%) in the PCI group and 17 patients (22.7%) in the non-PCI group. Regarding death as a competitive risk, patients who received PCI had a lower cumulative incidence of brain metastasis than those who did not (3-year: 14.7% vs. 22.7%; Gray test, P =0.007). Conclusions: When brain MRI was performed at diagnosis and pre-PCI, PCI could reduce the cumulative rate of brain metastases, but it did not achieve survival benefits for LS-SCLC patients.